2015
DOI: 10.1111/fire.12072
|View full text |Cite
|
Sign up to set email alerts
|

Investor Protection and the Role of Firm‐Level Financial Transparency in Attracting Foreign Investment

Abstract: We ask if companies can attract foreign equity capital by improving the transparency of their financial statements. Using a large panel of firms across 51 countries outside the United States, we show that the answer is yes, but only in countries with relatively high levels of investor protection. In countries with poor investor protection, unilaterally increasing firm‐level transparency has no effect on foreign ownership. Furthermore, our results indicate that in countries with higher levels of investor protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 74 publications
2
14
0
Order By: Relevance
“…Countries with strong investor protection are relatively low yielding transparency of information. Consistent with the results of Hansen et al (2015), the level of transparency tends to increase significantly in countries with stronger investor protection compared to countries with weaker investor protection. However, Jeanjean (2012) argue that the size of investor protection used by Houqe et al (2012) has some limitations.…”
Section: Additional Analysissupporting
confidence: 82%
“…Countries with strong investor protection are relatively low yielding transparency of information. Consistent with the results of Hansen et al (2015), the level of transparency tends to increase significantly in countries with stronger investor protection compared to countries with weaker investor protection. However, Jeanjean (2012) argue that the size of investor protection used by Houqe et al (2012) has some limitations.…”
Section: Additional Analysissupporting
confidence: 82%
“…This group of directors are unique because of their connections with another country, which may give room for adding new knowledge and expertise to the board. Nevertheless, they could be quite expensive because of the cost attributed to presence of the travelling expenses, distance and their non-familiarity with the nation of the firm where they are directors (Miletkov, 2013 …”
Section: Foreign Directors and Quality Of Financial Reportsmentioning
confidence: 99%
“…The evidence supports the hypothesis that foreign ownership participation increases the performance of firms. Moreover, while studies (MoIlah and Talukdar, 2007;Douma et al, 2002;Hansen et al, 2015) identify a positive impact from FPI to the company performance, some studies (for example, Barbosa and Louri, 2003;Khawar, 2003) identifies that there is no impact or the negative impact to the company performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the same vein, it is essential to note that it is rare that previous studies have employed both macro-economic variables and the company-specific factors to investigate whether both factors determine the FPI. For example, Hansen et al, (2015) concentrated only on firm-specific factors such as US Listing, Market Capitalization, Market Index, ROA, Big N Auditor, Leverage, Dividend Yield, Controlling Shareholder, Market to Book Value, Foreign Sales and Domestic Institutional Ownership to test the firm-level transparency. The study found that the firm-level transparency is positively related to foreign ownership.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation